On Location
VIII, 244 p.
Keywords: On Location: Heritage Cities and Sites merges the material and the social perspectives of preservation and historical interpretation in urban landscapes. The essays in this volume focus on the social life of historic cities and large-scale sites. They examine the ways that cities are dynamically changing as they are made and then remade by the people who inhabit or simply visit them, and concentrate on change, pluralism, and fragmentation. The strength of On Location: Heritage Cities and Sites is its comparative approach to both theory and grounded research. It includes an introductory essay that explains the heritage principle under study--the challenges of scale in the environment of a city or large complex--and its development as seen in the policy instruments of ICOMOS, UNESCO, and other major heritage organizations.The combination of wide-ranging case studies (including essays on North America, South America, Central America, the Middle East, and Europe) and the theoretical background make this volume an invaluable asset for researchers in archaeology, urban studies, art and architecture, cultural heritage, public policy, and tourism.